2017
DOI: 10.1016/j.ntt.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavioral change as a result of acute ethanol exposure in zebrafish: Evidence for a role for sonic hedgehog but not retinoic acid signaling

Abstract: BACKGROUND Developmental exposure to ethanol is recognized to produce long-term neurobehavioral impairment in multiple animal models. However, the molecular mechanisms underlying these deficits remain poorly understood. The present study was undertaken to ascertain whether two well-characterized targets of prenatal alcohol exposure, sonic hedgehog (Shh) and retinoic acid (RA), that induce the hallmark morphological phenotypes of fetal alcohol spectrum disorders (FASD), are involved in the generation of behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 49 publications
4
41
0
Order By: Relevance
“…Multiple studies have demonstrated that EAE affects zebrafish swimming behaviors (35)(36)(37)(38). To determine whether reduced locomotion was present in adults after EAE, we assessed activity level (35,(39)(40)(41)(42)(43)(44). Adult fish were subjected to a 10-minute habituation period, followed by a monitored locomotion assay.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated that EAE affects zebrafish swimming behaviors (35)(36)(37)(38). To determine whether reduced locomotion was present in adults after EAE, we assessed activity level (35,(39)(40)(41)(42)(43)(44). Adult fish were subjected to a 10-minute habituation period, followed by a monitored locomotion assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our laboratory analyzed novel tank diving behavior of juvenile fish exposed to 1% ethanol and demonstrated that binge‐like ethanol exposures cause alteration in behavior that is a correlate of anxiolytic (risk‐taking) behavior (Bailey et al, ; Burton et al, ). Other laboratories have also observed anxiolytic behaviors in larval and adult fish exposed to low‐dose CB1R agonists, and anxiogenic behavior when exposed to high‐dose agonists (Akhtar et al, ; Stewart & Kalueff, ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that signaling along the entire pathway may be inhibited. Interestingly, several studies have shown that the morphological and behavioral abnormalities associated with embryonic ethanol exposure in zebrafish could be rescued with shh mRNA overexpression (Burton, Zhang, Boa‐Amponsem, Mackinnon, & Cole, ; Loucks & Ahlgren, ; Zhang et al, ; Zhang, Turton, Mackinnon, Sulik, & Cole, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a growing number of behavioral assays in zebrafish that are relevant to the study of FASD (Burton et al . ). Social deficits are common in FASD (Kelly, Day & Streissguth ; Rasmussen et al .…”
Section: Discussionmentioning
confidence: 97%